Reducing the Allocation of Software Testing Demand: A Study on the Pros and Cons using STELA Tool - Oliveira, Flavia; Tiago, Leonardo; Chaves, Lennon (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2024: Anais do IX Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2024)
The speed at which new technology is developed and implemented in commercial products directly impacts the flow and rhythm of the software test field. In the context of global software development, different companies follow their unique approaches to assign their test demands to their employed testers; however, the dependency on a fully manual process that is prone to human error leads to a growing trend of possible issues, given that demand is expected to grow even more, making it even harder to keep up with them. To address this problem, we performed a study to determine the significance of the time gain and effort reduction when comparing the assignment task performed manually and automatically with support from the STELA tool developed within the research and development institute in which this study was conducted. Analysis of the data obtained through the collection of execution time and one-on-one interviews with the main assigners of a test team within the institute shows that using automation to simplify the assignment task not only makes it more efficient, with a reduction of 54% in the time invested when compared to manual execution, but also reduces the possibility of human error, even though the tool itself is prone to occasional errors.